The Modern Catholic Architecture of Post-war Germany: Rudolf Schwarz, Dominikus Böhm and other German architects - Ana Paula Borghi de Avelar; Michel Toussaint Alves Pereira (Histories of Postwar Architecture)
Germany was one of the countries that suffered the most from the destruction of wars, especially the Second World War, which devastated the country. Among the buildings for public use were churches. It was necessary to rebuild them as these buildings had a specific objective for that post-war era, to provide social and pastoral assistance to communities so suffering from the destruction. As a result, there was a large reconstruction movement mainly in the Rhineland region, led by architects Rudolf Schwarz and Dominikus Böhm, great names in German Catholic architecture. Schwarz and Böhm began their journeys in Catholic buildings during the "between wars" period, already involving the Liturgical Movement and the Modern Movement, in the first churches considered modern in Germany. They improved its development after the Second World War, influencing other architects. This article aims to provide a brief presentation of the development of German Catholic architecture, mainly in the post-Second World War, through a bibliographical review. It presents an architecture that was massively developed in a short period of time, improving the skills of architects and disseminating this architecture not only throughout the country but around the world.